Intricacy of Mitochondrial Dynamics and Antiviral Response During RNA Virus Infection - Singh, Sneha; Dirani, Karim; Kumar, Ashok (Frontiers in Virology, 2022)
Viruses are known to hijack the intracellular organelles, including mitochondria, endoplasmic reticulum, lipid droplets, and cytoskeleton to promote its replication. The host responds to invading viruses by mounting antiviral responses and rearrangement of its organelles. In particular, the mitochondria are one of the target organelles exploited by viruses and their proteins to suppress the host antiviral response. In this review, we have comprehensively summarized the impact of mitochondrial dynamics in modulating antiviral response during emerging and re-emerging RNA virus infections caused by genus Flavivirus (Dengue virus, Zika virus, Hepatitis C virus), and SARS-CoV-2, the causative agent of COVID-19 pandemic. In addition to knowledge gaps in mitochondria-virus interaction studies, we discuss recent advancements in therapeutics regulating the mitochondrial dynamics to combat viral infections.